Students’ Ability in Writing Descriptive Text Through Caption in Instagram - Annisa, Tiara; Rezeki, Yanti Sri; Surmiyati, Surmiyati (English Education : English Journal for Teaching and Learning, 2023)
The aim of this research was to find out how captioning on Instagram improved students' ability to write descriptive texts. The subject of this research were the students of the 10th class of MAN 1 Sambas. The subject of this study was the English subject students of MIPA class with a total of 23 students. The data was collected by two sources of data, there were qualitative and quantitative data. The quantitative data was taken from the tests.  The qualitative data was taken from observation notes. Data analysis showed that students' descriptive writing skills improved with each cycle. Student Test-1 results gave an average score of 61.6 students succeeded (17.3%) and 19 students failed (82.7%). Then, in the second cycle, the average student score (78.5) improved. She had 18 students (78.3%) who passed one criterion, and her 5 students (11.7%) who failed. Based on the observation notes, students' activity of using captions and writing descriptions on Instagram was very good, and students were enthusiastic about using Instagram in writing descriptive text. In other words, based on the results of qualitative and quantitative data, improvement was seen in students, especially in writing descriptive texts.